Pemaknaan Simbol Bendera One Piece sebagai Bentuk Resistensi Kultural: Studi Fenomenologis pada Komunitas Nakama Palembang - Marshella, Shelvi; Fera Indasari; Muslimin Ritonga (Institut Nalanda, 2026)
The phenomenon of popular culture symbols being used as a medium for socio-political expression has increasingly emerged among young people. This study aims to analyze the meaning of the One Piece flag (Jolly Roger) as a form of cultural resistance within the Nakama Palembang community. This research employs a qualitative approach using a phenomenological method to understand the subjective experiences of individuals in interpreting symbolic actions. Data were collected through in-depth interviews, participatory observation, and documentation. The findings indicate that the One Piece flag is interpreted not merely as a fictional symbol but as a representation of freedom, solidarity, and resistance against social injustice. The use of this symbol reflects a form of symbolic resistance that is subtle, non-confrontational, and rooted in everyday cultural practices. This study concludes that popular culture plays a significant role as an alternative space for youth to articulate social criticism and construct collective identity.